MDCT anatomy body - Romano, Luigia; Brancato, Giuseppe; SpringerLink (Online service). (Milan Springer, 2011)
Although already in its third decade, computed tomography (CT) remains a highly dynamic field. The rapid development of multidetector CT (MDCT) technology has challenged the radiological world, even more so with the increasing use of MDCT angiography and cardiac CT. State-of-the-art MDCT techniques have been further enhanced by innovative post-processing imaging software. The book MDCT Body Anatomy is designed to assist medical residents, imaging technicians, and clinicians. Its nearly 500 axial and multiplanar illustrations comprise a comprehensive MDCT anatomic atlas of the body able to provide prompt answers to imaging anatomy questions. The MDCT anatomy of the chest, abdomen, and pelvis is presented in three different parts, with every image containing an informative legend describing the anatomic section performed.
Lungs and Interstitial Network -- Airways -- Pulmonary Arteries and Veins -- Aorta and Supra-aortic Trunks -- Bronchial Arteries and Vena Cava -- Pleura and Pericardium -- Mediastinal Compartments, Lymphatic System, and Esophagus -- Heart and Coronary Arteries -- Chest Wall -- Diaphragm and Abdominal and Pelvic Walls -- Peritoneal Cavity -- Splanchnic Arteries -- Iliac Arteries and Abdominal Aorta -- Renal Arteries -- Inferior Vena Caval System -- Venous Portal Circle -- Abdominal Lymphatic System -- Gastroduodenal Tract -- Small Intestine -- Colon -- Liver -- Biliary System -- Spleen -- Extraperitoneal Spaces -- Pancreas -- Adrenal Glands -- Kidneys and Ureters -- Urinary Bladder -- Bony Pelvis -- Muscular Pelvis and Pelvic Floor -- Pelvic Space -- Female Pelvis: Uterus, Ovaries, and Ligaments -- Prostate and Seminal Vescicles.
Electronic reproduction.
Keywords: Human anatomy; Anatomy; Human body; Human physiology; Electronic books